Economic evaluation of ASCOT-BPLA: antihypertensive treatment with an amlodipine-based regimen is cost effective compared with an atenolol-based regimen. Issue 2 (4th October 2007) - Lindgren, P; Buxton, M; Kahan, T; Poulter, N R; Dahlöf, B; Sever, P S; Wedel, H; Jönsson, B; ,
Abstract : Objective: To compare the cost effectiveness of an amlodipine-based strategy and an atenolol-based strategy in the treatment of hypertension in the UK and Sweden. Design: A prospective, randomised trial complemented with a Markov model to assess long-term costs and health effects. Setting: Primary care. Patients: Patients with moderate hypertension and three or more additional risk factors. Interventions: Amlodipine 5–10 mg with perindopril 4–8 mg added as needed or atenolol 50–100 mg with bendroflumethiazide 1.25–2.5 mg and potassium added as needed Main outcome measures: Cost per cardiovascular event and procedure avoided, and cost per quality-adjusted life-year gained. Results: In the UK, the cost to avoid one cardiovascular event or procedure would be €18 965, and the cost to gain one quality-adjusted life-year would be €21 875. The corresponding figures for Sweden were €13 210 and €16 856. Conclusions: Compared with the thresholds applied by NICE and in the Swedish National Board of Health and Welfare's Guidelines for Cardiac Care, an amlodipine-based regimen is cost effective for the treatment of hypertension compared with an atenolol-based regimen in the population studied.